2017
DOI: 10.1016/j.jchb.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Association of five SNPs with human hair colour in the Polish population

Abstract: Twenty-two variants (single nucleotide polymorphisms - SNPs) of the genes involved in hair pigmentation (OCA2, HERC2, MC1R, SLC24A5, SLC45A2, TPCN2, TYR, TYRP1) were genotyped in a group of 186 Polish participants, representing a range of hair colours (45 red, 64 blond, 77 dark). A genotype-phenotype association analysis was performed. Using z-statistics we identified three variants highly associated with different hair colour categories (rs12913832:A>G in HERC2, rs1805007:T>C and rs1805008:C>T in MC1R). Two v… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
8
0
2
Order By: Relevance
“…Additional individual SNP frequencies were obtained primarily from the published literature and were entered into the ALFRED database ( https://alfred.med.yale.edu ) before it became static. A fourth amino acid substitution, rs1800401 (Arg305Trp), has been typed in the 1 KG samples but is not included here because it has been otherwise studied largely in samples defined by pigmentation phenotypes (eye, hair, skin color) in a few populations 3 , 24 , 25 . The rare amino acid change (Val443Ile) at SNP rs121918166 has only been studied on a small number of European populations 10 and studied for its effect on eye, hair, and skin color.…”
Section: Methodsmentioning
confidence: 99%
“…Additional individual SNP frequencies were obtained primarily from the published literature and were entered into the ALFRED database ( https://alfred.med.yale.edu ) before it became static. A fourth amino acid substitution, rs1800401 (Arg305Trp), has been typed in the 1 KG samples but is not included here because it has been otherwise studied largely in samples defined by pigmentation phenotypes (eye, hair, skin color) in a few populations 3 , 24 , 25 . The rare amino acid change (Val443Ile) at SNP rs121918166 has only been studied on a small number of European populations 10 and studied for its effect on eye, hair, and skin color.…”
Section: Methodsmentioning
confidence: 99%
“…The actual mutation rate of microhaplotype should be researched in several generations and many parent-child pairs. Moreover, the piSNPs of selected phenotypic microhaplotype loci were fully investigated in many genome-wide association studies (GWAS), and have proved they all had strong association with some visual characteristics [44][45][46][47][48][49]. For example, the hair color was one of the most visual characteristics and strongly controlled by genes.…”
Section: Discussionmentioning
confidence: 99%
“…The SNP rs16891982 of mh05pi001 was located on the SLC45A2 gene, which encoded the membraneassociated transporter protein and mediated the formation of melanin [45]. The study in population of the University of Arizona has shown that the SNP rs16891982 and the hair color yield an R 2 of 0.637, and the study of Polish has suggested there was a strong correlation between the SNP rs16891982 and the hair color [45,46]. The TYRP1 gene controlled a key enzymatic step in melanin biosynthesis, and the SNP rs13289810 of mh09pi001 located on TYRP1 gene had the strongest correlation with the blonde and dark hair [47].…”
Section: Discussionmentioning
confidence: 99%
“…DNA, RNA tests (DNA and RNA isolation from various biological materials), study of genetic variation using classical methods of molecular biology such as: PCR, real-time PCR, Sanger sequencing [18], high-resolution melting of PCR products (HRM) [3-4, 17, 21, 26, 44-45], Taq-Man probes, measurements of selected parameters of the tested material (fluorometric testing of the DNA concentration), separation of nucleic acids using horizontal, vertical, capillary electrophoresis, genomic DNA testing using microarrays (e.g. GWAS) [15-16, 20, 22-23], next generation sequencing (Illumina Platform, Nanopore Sequencing), gene expression testing (RNA-seq, microarray and qPCR) [46][47][48][49][50][51], epigenetic analysis (Chip-Seq, DNA methylation analysis, methylation RNA), microorganism genome analysis (de novo sequencing, variant calling) [44,[52][53][54][55][56][57], eukaryotes whole genome and targeting sequencing, aDNA analysis [58][59], human genome analysis (variant calling, NGS Target Enrichment, whole exome sequencing), amplicon sequencing, metagenomics and metabarcoding, bioinformatics analysis.…”
Section: External Biobank Activitymentioning
confidence: 99%
“…; DNA; the collection was created for the project TESTOPLEK; retrospective; anonymized; POPULOUS_ BLUL[3][4][15][16][17][18][19][20][21][22][23].…”
mentioning
confidence: 99%